(untitled) (Research, Society and Development, 2017)
The study evaluates a survey conducted on the last day of the course with 118 students of the last year of two undergraduate engineering courses in Brazil, it was 86 students of the 4th year (8th level or period) of the metallurgical engineering course and 32 students of the 3rd year (6th level) of course materials engineering, to teaching students how to use and interpret polarization curves for predictive and preventive action of corrosion and its chemical mechanisms. The time period was from February 2012 to December 2013 in just three semesters (no summer school). During the time which an educational institution holds classes was required all students to read content before and during class and then work in groups to complete problems and answer conceptual questions and practical pertaining to the material they read. Teachers spent class time answering students’ questions. These students’ post course ratings on the respondents specify their level of agreement or disagreement on a symmetric agree-disagree scale for a series of attitudes and skills competence statements using a Likert-type scale. The results indicated that the students experiencing using an active learning methodology had more confidence in their ability to perform and interpret chemical corrosion mechanisms. Additionally, these students’ attitude scores were positively. In some cases, as shown by the student experience survey, assessing students’ attitudes can be an effective solution to these methodological discuss the various methodological problems faced by classroom researchers and suggest that, in some problems. Conclusions are made on ways to overcome or minimize the problems based on difficulty in learning and its chemical corrosion mechanisms through an active learning methodology approach.